Perspectives pour une histoire des annonces publicitaires de la presse magazine - Laura Truxa (Contextes)
This article aims to outline ways of developing the historical study of the advertising content of magazines. Firstly, a review of the literature on the subject will provide a theoretical framework for this project, at the crossroads of the history of advertising, periodical studies and visual studies. Such an undertaking invites us to take into account both the commercial dimensions of advertisements and their aesthetic and material dimensions, including periodicity and repetitiveness. Given these specific features, and the massive quantity of advertisements available, the creation of a study corpus requires careful consideration. Several proposals and working hypotheses are reviewed here, with no claim to exhaustiveness. The final section looks at the methods best suited to the examination of these objects, and attempts to link content analysis with the material history of magazine advertisements.